Pneumomediastinum after transbronchial cryobiopsy - Emanuela Barisione; Rita Bianchi; Roberto Fiocca; Mario Salio (Monaldi Archives for Chest Disease, 2018)
Pneumomediastinum is defined as the presence of air or gas within the mediastinum and it rarely complicates bronchoscopy. We report, to our best knowledge, the first case of pneumomediastinum following a transbronchial cryobiopsy (TBLC). TBLC is considered a safe procedure as compared with both transbronchial biopsy and surgical lung biopsy. Systematic reviews, metanalysis and a Pubmed research, revealed that in literature no pneumomediastinum has been mentioned after TBLC. We report this case for to make it known to interventional pulmonologists the possibility that a pneumomediastinum can follow a TBLC. In our case the spontaneous resolution in few days did not require any intervention.